(untitled) (Ozone Therapy Global Journal, 2011)
Controlled ozone administration has been shown to promote an adaptation to oxidative stress by increasing endogenous antioxidant systems. In the present study, the effects of O2/O3 administration either prophylactically or therapeutically on the alterations of oxidant status in adjuvant-induced arthritis in rats have been studied. Seven groups of rats were used: 1) normal control group; 2) control arthritic group (21 days); 3) prophylactic ozone group: arthritic rats received fifteen intra-rectal applications of O2/O3 at 0.5, 0.7 and 1 mg/kg b.w. in a 5-6 mL volume starting one day before adjuvant inoculation and continued as five applications/week over 21 days; 4) oxygen group: received oxygen (vehicle of ozone) in a similar schedule to group 3; 5) control arthritic group (24 days); 6) therapeutic-ozone group: arthritic rats received 10 intra-rectal applications of O2/O3 at 0.5, 0.7 and 1 mg/kg b. w. in a 5-6 mL volume daily for 10 days starting fourteen days after adjuva nt i noculation; 7) oxygen-trea ted group: received oxygen in a similar schedule of group 6. The effect of O2/O3 administration was assessed by measuring: bloo d glutathione (GSH ), erythrocyte glutathione peroxidase and catalase activities, serum levels of protein thiols (PrSH), malondialdehyde (MDA) and nitrite/nitrate (NO2/NO3), as well as serum ceruloplasmin activity (CP). The present study showed that adjuvant-induced arthritis in rats caused a significant (p<0.05) reduction in blood GSH, serum PrSH levels and erythrocyte antioxidant enzyme activities a ccompanied b y a significant (p<0 .05) i ncreas e in s erum le vels of MDA, NO2/NO3 and CP activity. Ozone administration either prophylactically or therapeutically normalize blood GSH, serum PrSH and MDA levels and restored erythrocyte antioxidant enzyme activities. However ozone did not significantly (p>0.05) modify serum NO2/NO3 level in induced rat but significant (p<0.05) increase CP activity. So it could be concluded that O2/O3 oxidative preconditioning / postconditioning effectively modulate the antioxidant/oxidant balance associated with adjuvant arthritis model in rats.